Word Power Made Easy : The Complete Handbook for Building a Superior Vocabulary - Lewis, Norman, 1912-2006 (New York Pocket Books, 1978)
Exercises designed to develop vocabulary skills present words together with their pronunciations, definitions and use in sentences.
Keywords: Vocabulary